"You Can't Just Give Your Best Mate a Massive Hug Every Day": Young Men, Play and MDMA. (September 2015) - Farrugia, Adrian
This article has two main aims. First, it contributes to youth alcohol and other drug (AOD) research interested in pushing beyond simplistic accounts of peer pressure. Second, it provides an account of the enactment of masculinity in young men's drug consumption that allows for an engagement with practices rarely present in AOD research. I analyze interviews with 25 Australian young men (aged 16–19) about their MDMA/ecstasy consumption practices. I argue, common concepts such as "peer pressure" fail to grasp the complexity of sociality and drug consumption. Current understandings of the role of masculinity in young men's drug consumption also struggle to engage with the practices that appear in this article. Co-constituted capacities of communication, intimacy, and friendship all emerge in many of the accounts of these young men's MDMA consumption. I argue that in these events can be seen experimental practices in which young men play with the possibilities of life. In order to analyze the exchanges of sensation that shape these events, I work with Georg Simmel's notion of "play" re-enacted through a Deleuzian ontology of affective assemblages. This conceptual approach enacts the experiences these young men speak of as events in which they are able to play in assemblages that shape their affective capacities. Three themes are identified in the interview data. First, I discuss a desire for communication in which young men emphasize the pleasures of being able to communicate in new ways. Next, I analyze the role the place and time of consumption plays in co-constituting these social practices. Finally, I look at the pleasures associated with the breaking down of perceived ontological bodily boundaries. My analysis suggests that young men are able to play with drugs, friends, masculinity, and space–time in ways that make new and positive sensations, experiences, and affects possible.